2021
DOI: 10.3390/ijerph182412926
|View full text |Cite
|
Sign up to set email alerts
|

Working with Young People at Risk of Suicidal Behaviour and Self-Harm: A Qualitative Study of Australian General Practitioners’ Perspectives

Abstract: General Practitioners (GPs) play a crucial role in the identification and support of young people at risk of suicidal behaviour and self-harm; however, no studies have explored GPs’ perspectives, approaches, challenges, and resource needs when working with this cohort in an Australian setting. This was a qualitative study where fifteen GPs (Mage = 45.25 years) from multiple clinics in Western Australia took part in semi-structured interviews, and data were analysed thematically. Seven main themes were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
(139 reference statements)
1
2
0
Order By: Relevance
“…Young people have previously suggested that self‐help materials from GPs would be helpful and this aligns to our findings, however concerns about time in the consultation were noted 36 . GPs have highlighted the importance of communication and relationship building with young people at risk of self‐harm and it's important to know that young people in this study felt future GP‐led treatments should enable the building of rapport which may help with feelings of social connectedness 37 . In an Australian focus group study of young people about care for suicidal behaviour/self‐harm in primary care, participants described wanting to be shown how to use tangible resources in the consultation with a GP, but not all participants had personal experience of self‐harm 24 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Young people have previously suggested that self‐help materials from GPs would be helpful and this aligns to our findings, however concerns about time in the consultation were noted 36 . GPs have highlighted the importance of communication and relationship building with young people at risk of self‐harm and it's important to know that young people in this study felt future GP‐led treatments should enable the building of rapport which may help with feelings of social connectedness 37 . In an Australian focus group study of young people about care for suicidal behaviour/self‐harm in primary care, participants described wanting to be shown how to use tangible resources in the consultation with a GP, but not all participants had personal experience of self‐harm 24 .…”
Section: Discussionsupporting
confidence: 83%
“… 36 GPs have highlighted the importance of communication and relationship building with young people at risk of self‐harm and it's important to know that young people in this study felt future GP‐led treatments should enable the building of rapport which may help with feelings of social connectedness. 37 In an Australian focus group study of young people about care for suicidal behaviour/self‐harm in primary care, participants described wanting to be shown how to use tangible resources in the consultation with a GP, but not all participants had personal experience of self‐harm. 24 While practical resources are likely helpful for young people who have self‐harmed, GPs and family physicians should personalise them and offer distraction techniques to help the young person handle urges to self‐harm.…”
Section: Discussionmentioning
confidence: 99%
“…Approved therapeutics include several drugs administered to depressed patients to decrease the possibility of SI and SA, such as Lithium (mood-stabilizing drug), Clozapine (reduces suicidality, aggressive/impulsive behaviours), and Ketamine/Esketamine (antidepressant) [ 124 ]. An Australian study also showed the critical role of general practitioners in preventing suicide [ 125 ]. Drugs, social efforts, psychological awareness and guidance should be accompanied with a healthy lifestyle and integrated nutrition to resist SB ( Figure 4 ).…”
Section: Pharmacotherapymentioning
confidence: 99%